Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có (x - 2)2 = 0 và (x - 2)2 > 0 với ∀x ≠ 2 và
(3x - 5) = 3.2 - 5 = 1 > 0.
Do đó
= +∞.
b) Ta có (x - 1) và x - 1 < 0 với ∀x < 1 và
(2x - 7) = 2.1 - 7 = -5 <0.
Do đó
= +∞.
c) Ta có (x - 1) = 0 và x - 1 > 0 với ∀x > 1 và
(2x - 7) = 2.1 - 7 = -5 < 0.
Do đó
= -∞.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1^7+2^7+...+n^7=\frac{6p^4-4p^3+p^2}{3}\)
Trong đó \(p=1+2+...+n=\frac{n\left(n+1\right)}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a=\frac{0-1}{0-1}=1\)
\(b=\lim\limits_{x\rightarrow0}\frac{\frac{x^2}{\sqrt[3]{\left(1+x^2\right)^2}+\sqrt[3]{1+x^2}+1}}{x^2}=\lim\limits_{x\rightarrow0}\frac{1}{\sqrt[3]{\left(1+x^2\right)^2}+\sqrt[3]{1+x^2}+1}=\frac{1}{3}\)
\(c=\lim\limits_{x\rightarrow2}\frac{\sqrt{x+2}-2+\sqrt{x+7}-3}{x-2}=\lim\limits_{x\rightarrow2}\frac{\frac{x-2}{\sqrt{x+2}+2}+\frac{x-2}{\sqrt{x+7}+3}}{x-2}=\lim\limits_{x\rightarrow2}\left(\frac{1}{\sqrt{x+2}+2}+\frac{1}{\sqrt{x+7}+3}\right)\)
\(=\frac{1}{\sqrt{4}+2}+\frac{1}{\sqrt{9}+3}=\frac{5}{12}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\lim\limits_{x\rightarrow-2}\dfrac{2x^2+x-6}{x^3+8}=\lim\limits_{x\rightarrow-2}\dfrac{\left(2x-3\right)\left(x+2\right)}{\left(x+2\right)\left(x^2-2x+4\right)}\\ =\lim\limits_{x\rightarrow-2}\dfrac{2x-3}{x^2-2x+4}=-\dfrac{7}{12}\).
b) \(\lim\limits_{x\rightarrow3}\dfrac{x^4-x^2-72}{x^2-2x-3}=\lim\limits_{x\rightarrow3}\dfrac{\left(x^2+8\right)\left(x+3\right)\left(x-3\right)}{\left(x-3\right)\left(x+1\right)}\\ =\lim\limits_{x\rightarrow3}\dfrac{\left(x^2+8\right)\left(x+3\right)}{x+1}=\dfrac{51}{2}\).
c) \(\lim\limits_{x\rightarrow-1}\dfrac{x^5+1}{x^3+1}=\lim\limits_{x\rightarrow-1}\dfrac{\left(x+1\right)\left(x^4-x^3+x^2-x+1\right)}{\left(x+1\right)\left(x^2-x+1\right)}\\ =\lim\limits_{x\rightarrow-1}\dfrac{x^4-x^3+x^2-x+1}{x^2-x+1}=\dfrac{5}{3}\).
d) \(\lim\limits_{x\rightarrow1}\left(\dfrac{2}{x^2-1}-\dfrac{1}{x-1}\right)=\lim\limits_{x\rightarrow1}\left(\dfrac{2}{\left(x-1\right)\left(x+1\right)}-\dfrac{x+1}{\left(x-1\right)\left(x+1\right)}\right)\\ =\lim\limits_{x\rightarrow1}\dfrac{1-x}{\left(x-1\right)\left(x+1\right)}=\lim\limits_{x\rightarrow1}\dfrac{-1}{x+1}=-\dfrac{1}{2}\).
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a=\lim\limits_{x\rightarrow0}\frac{x^2}{x\left(\sqrt{1+x^2}+1\right)}=\lim\limits_{x\rightarrow0}\frac{x}{\sqrt{1+x^2}+1}=\frac{0}{2}=0\)
\(b=\lim\limits_{x\rightarrow1}\frac{\sqrt[3]{x+7}-2+2-\sqrt{5-x^2}}{x-1}=\lim\limits_{x\rightarrow1}\frac{\frac{x-1}{\sqrt[3]{\left(x+7\right)^2}+2\sqrt[3]{x+7}+4}+\frac{\left(x-1\right)\left(x+1\right)}{2+\sqrt{5-x^2}}}{x-1}\)
\(=\lim\limits_{x\rightarrow1}\left(\frac{1}{\sqrt[3]{\left(x+7\right)^2}+2\sqrt[3]{x+7}+4}+\frac{x+1}{2+\sqrt{5-x^2}}\right)=\frac{1}{12}+\frac{1}{2}=\frac{7}{12}\)
\(c=\lim\limits_{x\rightarrow0}\frac{2x}{x\left(\sqrt[3]{\left(1+x\right)^2}+\sqrt[3]{\left(1+x\right)\left(1-x\right)}+\sqrt[3]{\left(1-x\right)^2}\right)}=\lim\limits_{x\rightarrow0}\frac{2}{\sqrt[3]{\left(1+x\right)^2}+\sqrt[3]{\left(1+x\right)\left(1-x\right)}+\sqrt[3]{\left(1-x\right)^2}}=\frac{2}{3}\)
\(d=\frac{\sqrt[3]{6}}{0}=+\infty\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
Ta có: \(\lim _{x\to -\infty}\frac{(x^2-1)(1-2x)^5}{x^7+x+3}=\lim_{x\to -\infty}\frac{\frac{(x^2-1)(1-2x)^5}{x^7}}{\frac{x^7+x+3}{x^7}}\)
\(=\lim_{x\to -\infty}\frac{\left ( \frac{x^2-1}{x^2} \right )\left ( \frac{1-2x}{x} \right )^5}{1+\frac{1}{x^6}+\frac{3}{x^7}}=\lim_{x\to -\infty}\frac{\left ( 1-\frac{1}{x^2} \right )\left ( \frac{1}{x}-2 \right )^5}{1+\frac{1}{x^6}+\frac{3}{x^7}}\)
\(=\frac{1(-2)^5}{1}=-32\)
(Nhớ rằng \(\lim_{x\to \infty}\frac{1}{x}=0\) là được )
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
=
= -4.
b)
=
=
(2-x) = 4.
c)
=
=
=
=
.
d)
=
= -2.
e)
= 0 vì
(x2 + 1) =
x2( 1 +
) = +∞.
f)
=
= -∞, vì
> 0 với ∀x>0.
lim x → 1 x + 8 - 8 x + 1 5 - x - 7 x - 3 = 7 12